Usability Analysis of Library Websites of National Institutes of Technology of India: An Evaluation - Verma, Nitesh Kumar; Kumar, Nilesh (Journal of Information and Knowledge, 2020)
To maintain the standard, design and structure of Indian academic library websites, regular assessment of library web portals to increase their usability and accessibility is necessary. The purpose of this study is to evaluate the usability, efficiency, and effectiveness of thirty National Institutes of Technology (NIT) Libraries websites in India. Most of the selected Libraries websites are very simple and had very basic and common usability features in terms of General Information, Available library services, about website, Website search facility, Use of web 2.0 applications, Page load time and Mobile friendly test, etc. There is enormous scope for improvement. Findings of the study will help to improve upon the usability features of selected libraries websites that will finally benefit the library users who are using library facilities and services remotely. Study will also help the webmasters to check their websites on timely basis to increase usability scores based on online usability tools.